Peningkatan Akuntabilitas Publik Melalui Sistem Informasi Akuntansi pada Pondok Pesantren Salafiyah - Dwi Sulistiani (Akuntabilitas, 2019)
This study aims to determine the cash out transactions that occur in the Sabilurrosyad Islamic boarding school, analyze the internal control system, then compile the AIS cash outflow chart for the Sabilurrosyad boarding school so that it can increase public accountability. The research method is descriptive qualitative method using case studies. The results of the study indicate that internal control is still not good as evidenced by the existence of multiple tasks. Understanding of risk is still not understood by the leaders of Islamic boarding schools, information and communication is unclear. Monitoring has been carried out with the existence of monthly and annual financial reports, but it has not been compiled according to the accounting standards that should be. The flow chart has not been created so that the results of this study are in the form of a cash flow chart AIS can be used by the Sabilurrosyad boarding school.